Just another Ungleichung

Behauptung:

$$(1+x)^n \leq 1+(2^n – 1) \cdot x \quad\quad 0\leq x\leq 1 \quad\quad n\geq 1$$



Beweis:

Induktionsanfang: n = 1

$$(1+x)^1~=~1+x~\leq~1+x~=~1+(2^1 -1)\cdot x$$

Induktionsschritt: A(n) => A(n+1)

$$\begin{align*}(1+x)^{n+1} &=~(1+x)^n\cdot (1+x)\\ &\leq~(1+(2^n -1)\cdot x)\cdot (1+x)\\ &=~1+2^n\cdot x – x + x +2^n\cdot x^2 -x^2\\ &=~1+2^n\cdot x +(2^n \cdot x -x)\cdot x\\ &\leq~ 1+2^n \cdot x +2^n \cdot x -x\\ &=~ 1+ 2\cdot 2^n\cdot x – x\\ &=~ 1+2^{n+1}\cdot x – x\\ &=~1+(2^{n+1}-1)\cdot x\end{align*}$$

q.e.d.

Weiterlesen: n und sqrt(n)